Pengembangan Media Pembelajaran Flipbook Digital Fisika Untuk Siswa Kelas X pada Materi Usaha dan Energi SMA Negeri 1 Matan Hilir Utara - Yuniarrahmana, Saprida; Matsun, Matsun; Hakim, Sy Lukman (PRISMA FISIKA, 2021)
This study aims to determine: (1) the feasibility of digital physics flipbook media for class X students on work and energy at SMA Negeri 1 Matan Hilir Utara according to material experts, (2) the feasibility of digital physics flipbook media for class X students on work and energy. According to media experts, SMA Negeri 1 Matan Hilir Utara, and (3) student responses after being given a physical flipbook learning media for class X students in the work and energy of SMA Negeri 1 Matan Hilir Utara. This type of research is Research & Development (R&D) research with the model used is the ADDIE model. The test subjects in this study were students of class X SMA Negeri 1 Matan Hilir Utara with a total of 20 students. With the results of the trials carried out, it was found that: (1) the feasibility of digital flipbook learning media according to material experts received very decent criteria, with an average score of 80%, (2) the feasibility of digital flipbook learning media according to media experts received decent criteria, with an average an average score of 75%, (3) the results of field trials on digital flipbook learning media for work and energy by distributing student response questionnaires. The average percentage score obtained by this digital flipbook learning media is 88%, which means that the student response interpretation criteria are included in the criteria for strongly agree. Kata Kunci: Learning Media, Digital Flipbook, work and energy